The big picture with Ricky Carandang. - Carandang, Ricky (SSS series on the Philippine economy, 2010)
5 part series on the Philippine economy. Experts in the field were invited to share thoughts on the current economic issues, what was done in the past to address the issues and what current administration can do to solve these issues.